2016
DOI: 10.1017/s0033291716002737
|View full text |Cite|
|
Sign up to set email alerts
|

Bitemporal v. high-dose right unilateral electroconvulsive therapy for depression: a systematic review and meta-analysis of randomized controlled trials

Abstract: High-dose unilateral ECT does not differ from moderate-dose bitemporal ECT in antidepressant efficacy but has some cognitive advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 56 publications
2
94
1
2
Order By: Relevance
“…Cognitive impairment and effectiveness of treatment are both related to the stimulus dose, especially for right unilateral ECT,2, 3 and there is a clinical trade-off between the two effects; a meta-analysis 12 found that high-dose right unilateral ECT was as effective as moderate-dose bitemporal ECT, with a similar cognitive effect profile for anterograde memory and verbal fluency; however, right unilateral ECT might have benefits for retrograde autobiographical memory and reorientation time after seizure. Ultra-brief pulse right unilateral ECT (pulse width 0·3 ms) was associated with less cognitive impairment but was also less effective than brief pulse right unilateral ECT (pulse width 1·0–1·5 ms) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment and effectiveness of treatment are both related to the stimulus dose, especially for right unilateral ECT,2, 3 and there is a clinical trade-off between the two effects; a meta-analysis 12 found that high-dose right unilateral ECT was as effective as moderate-dose bitemporal ECT, with a similar cognitive effect profile for anterograde memory and verbal fluency; however, right unilateral ECT might have benefits for retrograde autobiographical memory and reorientation time after seizure. Ultra-brief pulse right unilateral ECT (pulse width 0·3 ms) was associated with less cognitive impairment but was also less effective than brief pulse right unilateral ECT (pulse width 1·0–1·5 ms) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…82 In the past, there was controversy as to the comparative efficacy of RUL vs. bitemporal ECT, the latter being considered more effective. However, recent meta-analyses have found that high-dose RUL and bitemporal ECT are equally effective, 17,85 and considered that previous RUL ECT trials that used lower doses (e.g., less than six times the seizure threshold) might have underestimated its treatment effects. More recently, bifrontal ECT has been introduced as a form of ECT with efficacy comparable to that of bitemporal ECT, but fewer side effects.…”
Section: Convulsive Modalitiesmentioning
confidence: 99%
“…For convulsive therapies, there might be a trade-off between using higher doses to produce greater clinical benefits but with additional side effects. 85 More recently, computational models have been used to quantify electric fields (EFs) in brain regions of interest (ROIs). In fact, there are freely available software packages that perform electric field simulations using high-quality MRI images (templates or individualized) via a series of steps: 1) automated tissue segmentation of structural MRI; 2) meshing of the different tissue compartments to form a 3D model of the head and brain; 3) processing DTI data to extract white-matter anisotropic conductivity values; 4) incorporating electrodes and the TMS coil on the head model; 5) assigning appropriate electrical properties for the tissues and electrode/coil; 6) solving for the electric field and current density, via numerical methods such as finite element or boundary element methods; and 7) exporting, visualizing, and/or transforming electric field distribution to standard space for group analysis.…”
Section: Convulsive Modalitiesmentioning
confidence: 99%
“…Brief pulse (1.0 ms), high dose unilateral ECT is as effective as the original bitemporal placement of electrodes, with fewer cognitive side effects, including on autobiographical memory 28. These effects are further reduced by using ultrabrief pulse (0.3 ms) ECT, though it has slightly lower remission rates 29…”
Section: No— Sameer Jauhar and Declan M Mcloughlinmentioning
confidence: 99%